Formulasi Dan Uji Stabilitas Fisik Sediaan Masker Gel Peel-Off Ekstrak Etanol Umbi Porang (Amorphophallus Muelleri) Sebagai Antioksidan - Wahyu Firmansyah; Gina Septiani Agustien; Nitya Nurul Fadilah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
A peel-off gel mask is a cosmetic used for facial skin care in the form of a gel. Porang tuber extract peel-off gel mask (Amorphophallus muelleri) contains polyphenolic tannins which are efficacious as antioxidants. This study aims to determine the formulation of peel-off gel mask preparations of porang tuber extract and to determine the physical evaluation and antioxidant test of peel-off gel mask preparations of porang tuber extract using the DPPH method. Experimental formulation method with 7% polyvinyl alcohol (PVA) base. The active ingredient used is porang tuber extract with a concentration of 0.5% (F1), 1% (F2), and 1.5% (F3). Evaluation of the preparations carried out were organoleptic test, homogeneity test, pH test, drying preparation test, spreadability test, hedonic test and stability test. Based on the results of the stability test, it was shown that the peel-off gel mask preparation of porang tuber ethanol extract at various concentrations met the requirements for each test parameter. The antioxidant test results showed that F1 had an IC50 value of 48.75 ppm, F2 had an IC50 value of 43.18 ppm, and F3 had an IC50 value of 11.15 ppm which means that the three formulas have very strong antioxidant activity.